The cultural and symbolic significance of the African rhinoceros: a review of the traditional beliefs, perceptions and practices of agropastoralist societies in southern Africa - Boeyens, J. C. A.; van der Ryst, M. M. (Southern African Humanities, 2014)
A study of ethnobiological, archaeological, linguistic and historical ethnographic data shows that notions about the cultural and symbolic significance of the African rhinoceros were widely shared among southeastern Bantu speakers and had considerable time depth. African farming communities could draw upon the traits of both the more aggressive and solitary black rhino (Diceros bicornis) and the more sociable and territorial white rhino (Ceratotherium simum) in their conceptualisation of the qualities of leadership. The Mapungubwe gold rhino served as an emblem of sacred leadership in a class-based society. In less-stratified Sotho-Tswana society, the importance of this pachyderm was reflected in its appropriation as a leadership referent in chiefly praise poems, the use of rhino figurines as didactic tools during initiation schools, as well as a plethora of vernacular names and a complex folk taxonomy. Meat cut from the breast of the rhino was the preserve of a chief and a special club of rhino horn was widely employed as a marker of chiefly status. Rhino horns and bones also featured in rainmaking rituals. Monoliths adorning the central courts of nineteenth-century Tswana towns, as well as the walls or courts of Zimbabwe culture and Venda capitals, most probably signified rhino horns, thereby architecturally encapsulating the key qualities of power, danger and protection traditionally associated with African leadership.